Nanocellulose Length Determines the Differential Cytotoxic Effects and Inflammatory Responses in Macrophages and Hepatocytes. Issue 38 (6th August 2021) - Li, Jiulong; Wang, Xiang; Chang, Chong Hyun; Jiang, Jinhong; Liu, Qi; Liu, Xiangsheng; Liao, Yu‐Pei; Ma, Tiancong; Meng, Huan; Xia, Tian
Abstract: Nanocellulose including cellulose nanocrystal (CNC) and cellulose nanofiber (CNF) has attracted much attention due to its exceptional mechanical, chemical, and rheological properties. Although considered biocompatible, recent reports have demonstrated nanocellulose can be hazardous, including serving as drug carriers that accumulate in the liver. However, the nanocellulose effects on liver cells, including Kupffer cells (KCs) and hepatocytes are unclear. Here, the toxicity of nanocellulose with different lengths is compared, including the shorter CNCs (CNC‐1, CNC‐2, and CNC‐3) and longer CNF (CNF‐1 and CNF‐2), to liver cells. While all CNCs triggered significant cytotoxicity in KCs and only CNC‐2 induced toxicity to hepatocytes, CNFs failed to induce significant cytotoxicity due to their minimal cellular uptake. The phagocytosis of CNCs by KCs induced mitochondria ROS generation, caspase‐3/7 activation, and apoptotic cell death as well as lysosomal damage, cathepsin B release, NLRP3 inflammasome and caspase‐1 activation, and IL‐1β production. The cellular uptake of CNC‐2 by hepatocytes is through clathrin‐mediated endocytosis, and it induced the caspase‐3/7‐mediated apoptosis. CNC‐2 shows the highest levels of uptake and cytotoxicity among CNCs. These results demonstrate the length‐dependent mechanisms of toxicity on liver cells in a cell type‐dependent fashion, providing information to safely use nanocellulose for biomedical applications. Abstract : Nanocellulose induces length‐ and cell type‐dependent toxic effects on macrophages and hepatocytes. The phagocytosis of cellulose nanocrystal (CNC) by Kupffer cells induces mtROS generation, caspase‐3/7 activation, and apoptosis. Additionally, the phagocytosed CNC triggers lysosomal damage, cathepsin B release, caspase‐1 activation, and IL‐1β production. The limited cellular uptake of CNC‐2 by hepatocytes through clathrin‐mediated endocytosis induces the caspase‐3/7‐mediated apoptosis.